ANALISIS PENGARUH STRES KERJA DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI ” (Studi Kasus di Sekretariat Daerah Kabupaten Batang) (Students' Journal of Economic and Management, 2013)
The purpose of this study is to examine and analyze whether there is influence of Job Stress and Leadership Style on Job Satisfaction with mediation motivation. the Regional Secretariat Batang. Engineering test data used in this study include validity, reliability testing, regression analysis, Model Test (Test F and R2) and the mediation test to prove the research hypothesis. Data collected was tested for validity by factor analysis method and tested reliability with coefficient alpha (Cronbach alpha). The data is valid and reliability test results showed the number 0.928 to the variable Job Stress, 0,880 for Leadership Style variable, 0.916 to 0.931 for the variable Motivation and Job Satisfaction variable. The results of the analysis and discussion showed that the negative effect on Occupational Stress Motivation, Leadership Styles positive effect on motivation and motivation is not proven to mediate the effect of Job Stress and Leadership Style on Job Satisfaction. Keywords: Job Stress, Leadership Style, Motivation and Job Satisfaction.